The ENCODE Portal as an Epigenomics Resource. Issue 1 (21st November 2019) - Jou, Jennifer; Gabdank, Idan; Luo, Yunhai; Lin, Khine; Sud, Paul; Myers, Zachary; Hilton, Jason A.; Kagda, Meenakshi S.; Lam, Bonita; O'Neill, Emma; Adenekan, Philip; Graham, Keenan; et al.
Abstract: The Encyclopedia of DNA Elements (ENCODE) web portal hosts genomic data generated by the ENCODE Consortium, Genomics of Gene Regulation, The NIH Roadmap Epigenomics Consortium, and the modENCODE and modERN projects. The goal of the ENCODE project is to build a comprehensive map of the functional elements of the human and mouse genomes. Currently, the portal database stores over 500 TB of raw and processed data from over 15, 000 experiments spanning assays that measure gene expression, DNA accessibility, DNA and RNA binding, DNA methylation, and 3D chromatin structure across numerous cell lines, tissue types, and differentiation states with selected genetic and molecular perturbations. The ENCODE portal provides unrestricted access to the aforementioned data and relevant metadata as a service to the scientific community. The metadata model captures the details of the experiments, raw and processed data files, and processing pipelines in human and machine‐readable form and enables the user to search for specific data either using a web browser or programmatically via REST API. Furthermore, ENCODE data can be freely visualized or downloaded for additional analyses. © 2019 The Authors. Basic Protocol : Query the portal Support Protocol 1 : Batch downloading Support Protocol 2 : Using the cart to download files Support Protocol 3 : Visualize data Alternate Protocol : Query building and programmatic access